A progress report on the evaluation of metal cutting coolants - Chater, T. (College of Aeronautics, 1965)
An intensive investigation into the grinding process was carried out in The College of Aeronautics Machine Tools Laboratory during 1955-6. The outcome of this work was a method of evaluating the efficiency of grinding wheel specifications. Briefly, this consists of holding all other conditions constant and changing the grinding wheel specification from the grinding tests made then the rate of grinding wheel wear and the maximum metal removal rate is ascertained. This data may be used to compare one specification to another. The method has been used to select the best wheel specification for a wide range of materials, especially the more difficult machinable alloys examples being the stainless steel and the alloys intended for use at high temperatures. During the ten years since 1956 the method has been further developed by retaining the grinding wheel specification constant and varying the work piece material to determine the grinding machinability of alloys, and also a much more valuable criteria of the grinding process - the efficiency of coolants when used in the grinding process. This work on coolant evaluation has received detailed and extensive attention. The results of tests carried out on more than 300 coolant samples ranging from oil based and water soluble coolants with varying percentages of addative has revealed that the coolant can increase the life of the grinding wheel face by 10 times. All results found from the method of evaluation are expressed in terms of maximum metal removal rate and volume of metal which may be removed at maximum rate.